Unemployment challenges in the EU Social Security - Pazó Argibay, José Manuel (LABOS Revista de Derecho del Trabajo y Protección Social, 2024)
Unemployment regulation in European Union has been configured on a coordination technique that doesn’t act on the content of each of the national legislations searching an uniform legislation, but setting rules to accommodate national regulations with the guarantee of free movement of workers. Despite the regulatory effort, these provisions sometimes present certain dysfunctions. This work analyzes the particular provisions applicable to unemployment benefits contained in the EU Regulation and their modification proposals, highlighting most controversial aspects and proposing alternatives to improve them.